INSTRUCTION AND AGE IN THE ACQUISITION OF NEGATION IN ENGLISH AS A THIRD LANGUAGE - Ruiz de Zarobe, Yolanda (Linguistica Atlantica, 2003)
This paper reports the findings of a study that examined the relationship between the age of introduction of English as a foreign language in a formal instructional setting and the acquisition of negation in English. Participants were 81 bilingual (Basque/Spanish) students who had begun learning English at different ages but under conditions of equal exposure time to the foreign language. In both production tasks, younger students produced a high percentage of externally negated constructions and unanalysed negative particles, while older students made a better use of the full auxiliary system, including the ability to inflect correctly for number and time reference. These results may be accounted for considering age and cognitive maturity. The results indicate that age is positively related to the acquisition of the difIerent developmental sequences in English.